Validity and Students’ Responses to Interactive E-Modules Based on Inquiry Learning Assisted by the Virtual Laboratory on Static Electricity - Fatmila Nurliani; Irma Rahmawati; Suryandari Suryandari (Universitas Lambung Mangkurat, 2023)
The development of an interactive e-module based on inquiry learning assisted by a virtual laboratory on static electricity was created to produce innovative learning media and follow the trends of the 5.0 learning era. Therefore, the research was directed at validating the material and media in related modules and measuring students' responses to the modules being developed. This research used Borg and Gall's ten-step research and development model. However, the Borg and Gall development model in this study was modified into six research steps: research and information collecting, planning, developing preliminary from product, preliminary field testing, main product revision, and main field testing. The research respondents were 30 students from class XII IPA at MAN 1 Hulu Sungai Tengah. The product validity results by material experts reached V Aiken's 0.91, and media experts reached V Aiken's 0.96, both of which are in the high validity category. The results of student responses show an average value of 90%, equivalent to a very good product category. Thus, the interactive e-module based on inquiry learning assisted by the virtual laboratory on static electricity is included in the “strongly agree” category to be suitable for use.